Method for detecting content of iron oxide impurity in brown aluminum oxide

Through a simple chemical detection method, using common reagents and equipment, the problem of complex and high cost of detecting iron oxide impurities in brown corundum in the prior art is solved, and a fast, simple and economical detection effect is achieved.

CN119643780APending Publication Date: 2025-03-18JIANGMEN ANNUOTE COOKING UTENSILS MFG
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411623645.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The method of detecting Fe2O3 content in iron oxide impurity in brown corundum in the prior art is complex and costly, and it is difficult to meet the rapid, simple and economical testing needs in the industry.

Method used

A method for detecting the content of iron oxide impurities in brown corundum is proposed. Through sampling, grinding, drying, making sample liquid, iron oxide ion titration and other steps, the detection is achieved using common chemical reagents and equipment, and the use of expensive instruments is avoided.

Benefits of technology

It realizes rapid, simple and economical testing of iron oxide impurities content in brown corundum, reduces detection costs, and is suitable for widespread applications in industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119643780A_ABST
    Figure CN119643780A_ABST
Patent Text Reader

Abstract

The invention discloses a method for detecting the content of iron oxide impurities in brown aluminum oxide. The method comprises the following steps: sampling; preparing a sample solution; obtaining the volume of the sodium thiosulfate solution consumed by the sample solution; obtaining the volume of the sodium thiosulfate solution consumed by the purified water; and determining the percentage content of the iron oxide impurity in the brown aluminum oxide. According to the method for detecting the content of the iron oxide impurity in the brown aluminum oxide, the content of the impurity ferric oxide in the brown aluminum oxide can be simply and quickly detected at very low cost under the conditions that expensive instruments are not used and tedious and complicated operation steps are not needed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of detection technology, and in particular to a method for detecting the content of iron oxide impurities in brown corundum. Background Art

[0002] Sandblasting is the most commonly used process in metal surface treatment, and brown corundum is one of the most commonly used abrasives in sandblasting. The quality of brown corundum has a great influence on the efficiency, cost and effect of sandblasting. Therefore, the quality control of brown corundum abrasive has become a key point in sandblasting.

[0003] Fe2O3 is an impurity of brown corundum. A high content of Fe2O3 will reduce the hardness of brown corundum and make it easy to break during sandblasting, thus reducing its durability. Frequent replacement of abrasives will increase process costs. As shown in Table 1 below, GB / T 2478-2022 "Common Abrasive Brown Corundum" specifies the content of Fe2O3 impurities in brown corundum.

[0004]

[0005] GB / T 3043-2017 "Chemical Analysis Methods for Brown Corundum, a Common Abrasive" stipulates the detection of Fe2O3 in brown corundum. The method described in the standard requires complex pre-treatment and involves high-temperature melting. The detection steps are also cumbersome and require a long detection time and professional testers. Although there are XRF and XRD equipment on the market that can detect the content of Fe2O3 in brown corundum, these equipment are expensive and require professional operation. Most units do not use equipment detection methods due to high prices and high maintenance costs.

[0006] Therefore, it is very necessary to develop a simple, fast and low-cost method for detecting ferric oxide as an impurity in brown corundum. Summary of the invention

[0007] The present application aims to solve at least one of the technical problems existing in the prior art. To this end, the present application proposes a method for detecting the content of iron oxide impurities in brown corundum, which can detect the content of impurity ferric oxide in brown corundum simply, quickly and at a very low cost without using expensive instruments and cumbersome and complicated operation steps.

[0008] The method for detecting the iron oxide impurity content in brown corundum according to the embodiment of the present application comprises: Sampling: Sampling and reducing the brown corundum batch to be tested to obtain brown corundum samples; Prepare the sample solution: weigh a brown corundum sample with a mass of M and put it into a reactor, add deionized water and concentrated hydrochloric acid, react to obtain a sample solution with a volume of V1; Obtain the volume of sodium thiosulfate solution consumed by the sample solution: draw a sample solution with a volume of V2 into a conical flask, add hydrochloric acid and ammonium persulfate, heat and evaporate, oxidize all the iron ions in the sample solution to trivalent iron ions, add potassium iodide after cooling, add hot water, add starch indicator, and titrate with a sodium thiosulfate solution with a concentration of C1 until the blue color disappears as the end point, and the volume of sodium thiosulfate solution consumed by the sample solution is V3; Obtain the volume of sodium thiosulfate solution consumed by pure water: draw pure water with a volume of V2 into a conical flask, add hydrochloric acid and ammonium persulfate, heat and evaporate, add potassium iodide after cooling, add hot water, add starch indicator, and titrate with sodium thiosulfate solution with a concentration of C1 until the blue color disappears as the end point, and the volume of sodium thiosulfate solution consumed by pure water is V4; Determine the percentage of iron oxide impurities in brown corundum: Determine the percentage of iron oxide impurities in brown corundum based on M, V1, V2, V3, C1 and V4.

[0009] According to the method for detecting the iron oxide impurity content in brown corundum described in the embodiment of the present application, there are at least the following beneficial effects: the method for detecting the iron oxide impurity content in brown corundum described in the embodiment of the present application can detect the content of the impurity ferric oxide in brown corundum simply, quickly and at a very low cost without using expensive instruments and without cumbersome and complicated operating steps.

[0010] According to the method for detecting the iron oxide impurity content in brown corundum described in the embodiment of the present application, during sampling, the brown corundum of the batch to be tested is sampled and divided until a 100g brown corundum sample is obtained.

[0011] According to the method for detecting the iron oxide impurity content in brown corundum described in the embodiment of the present application, after completing the sampling and before preparing the sample liquid, it also includes: grinding: grinding 100g of brown corundum sample; drying: drying the brown corundum sample.

[0012] According to the method for detecting the iron oxide impurity content in brown corundum described in the embodiment of the present application, during grinding, 100 g of brown corundum sample is put into a grinder for grinding, and ground until the particle size of the brown corundum sample is less than 10 μm.

[0013] According to the detection method for the iron oxide impurity content in brown corundum described in the embodiment of the present application, in the preparation of the sample solution, 10 g of brown corundum sample is weighed and placed in the lining of the reactor, 20 mL of deionized water is added to the lining of the reactor, and 50 mL of concentrated hydrochloric acid is slowly added along the edge of the lining of the reactor, the lining of the reactor is covered, the reactor is tightened, and it is placed in an oven for reaction to obtain 250 mL of sample solution.

[0014] According to the method for detecting the iron oxide impurity content in brown corundum described in the embodiment of the present application, in preparing the sample solution, the reaction temperature is 170-210° C. and the reaction time is 5-8 hours.

[0015] According to the method for detecting the iron oxide impurity content in brown corundum described in the embodiment of the present application, in the preparation of the sample solution, after the reaction is completed, the sample solution is filtered using a rapid filter paper, and the lining of the reactor is fully washed, and finally the volume is fixed to a 250 mL volumetric flask.

[0016] According to the method for detecting the content of iron oxide impurities in brown corundum described in the embodiment of the present application, in obtaining the volume of sodium thiosulfate solution consumed by the sample solution, a volume of 50 mL of the sample solution is drawn into a 250 mL conical flask, 6 mL of (1+1) hydrochloric acid and 0.5 g of ammonium persulfate are added, and the sample solution is heated and evaporated to 10 mL to oxidize all the iron ions in the sample solution to trivalent iron ions. After cooling, 2 g of potassium iodide is added, 50 mL of 70°C hot water is added, 1 mL of 1% starch indicator is added, and the solution is titrated with 0.1 mol / L sodium thiosulfate solution until the blue color disappears as the end point, and the volume of the sodium thiosulfate solution consumed by the sample solution is V3.

[0017] According to the method for detecting the content of iron oxide impurities in brown corundum described in the embodiment of the present application, in obtaining the volume of sodium thiosulfate solution consumed by pure water, 50 mL of pure water is absorbed into a 250 mL conical flask, 6 mL of (1+1) hydrochloric acid and 0.5 g of ammonium persulfate are added, and the mixture is heated and evaporated to 10 mL. After cooling, 2 g of potassium iodide is added, 50 mL of 70°C hot water is added, 1 mL of 1% starch indicator is added, and the mixture is titrated with 0.1 mol / L sodium thiosulfate solution until the blue color disappears as the end point, and the volume of the sodium thiosulfate solution consumed by the pure water is V3.

[0018] According to the method for detecting the content of iron oxide impurities in brown corundum described in the embodiment of the present application, in determining the percentage content of iron oxide impurities in brown corundum, the following steps are included: Obtaining the percentage of trivalent iron ions in the sample solution: according to V2, V3, C1 and V4, obtaining the percentage of trivalent iron ions C2 in the sample solution; Determine the percentage of iron oxide impurities in brown corundum: According to C2, M, and V1, determine the percentage W of iron oxide impurities in brown corundum.

[0019] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions of the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0021] Figure 1 A flow chart of a method for detecting the content of iron oxide impurities in brown corundum according to some embodiments of the present application; Figure 2 A flow chart of a method for detecting the content of iron oxide impurities in brown corundum according to some embodiments of the present application; Figure 3 This is a flow chart of a method for detecting the iron oxide impurity content in brown corundum according to some embodiments of the present application. DETAILED DESCRIPTION

[0022] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application.

[0023] In the description of the present application, it should be understood that descriptions involving orientation, such as up, down, front, back, left, right, etc., indicating orientations or positional relationships, are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.

[0024] In the description of this application, "several" means one or more, "more" means more than two, "greater than", "less than", "exceed", etc. are understood to exclude the number itself, and "above", "below", "within", etc. are understood to include the number itself. If there is a description of "first" or "second", it is only used for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.

[0025] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "installation, connection and connection" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be an indirect connection through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0026] Reference Figure 1 The embodiment of the present application provides a method for detecting the iron oxide impurity content in brown corundum, including but not limited to step S110, step S120, step S130, step S140 and step S150.

[0027] Step S110, sampling: sampling and reducing the brown corundum of the batch to be tested to obtain brown corundum samples.

[0028] Specifically, according to GB / T 4676-2018 “General Abrasive Sampling Method”, the brown corundum of the batch to be tested is sampled and reduced until a 100g brown corundum sample is obtained.

[0029] Step S120, preparing a sample solution: weigh a brown corundum sample with a mass of M and put it into a reaction kettle, add deionized water and concentrated hydrochloric acid, react, and obtain a sample solution with a volume of V1.

[0030] Specifically, weigh 10g of brown corundum sample and put it into the reactor liner, add 20mL of deionized water to the reactor liner, and slowly add 50mL of concentrated hydrochloric acid along the edge of the reactor liner, cover the reactor liner, tighten the reactor, put it into an oven for reaction, and obtain 250mL of sample solution. Wherein, during the reaction process, the reaction temperature is 170-210℃, and the reaction time is 5-8 hours, so as to ensure the stability of the reaction and improve the accuracy of the detection. Further, after the reaction is completed, the sample solution is filtered using a quick filter paper, and the reactor liner is fully washed, and finally the volume is set to a 250mL volumetric flask. By filtering the sample solution, the solids in the sample solution can be prevented from affecting the accuracy of subsequent detection.

[0031] Reference Figure 2 , after completing step S110 and before performing step S120, further comprising: Step S210, grinding: grinding 100 g of brown corundum sample; Step S220, drying: drying the brown corundum sample.

[0032] Specifically, 100 g of brown corundum sample is put into a grinder for grinding, and ground until the particle size of the brown corundum sample is less than 10 μm; then the ground 100 g of brown corundum sample is put into an oven for drying to remove moisture in the brown corundum sample to ensure the accuracy of subsequent testing.

[0033] Step S130, obtaining the volume of sodium thiosulfate solution consumed by the sample solution: aspirate a sample solution with a volume of V2 into a conical flask, add hydrochloric acid and ammonium persulfate, heat and evaporate, so that all iron ions in the sample solution are oxidized to trivalent iron ions, add potassium iodide after cooling, add hot water, add starch indicator, and titrate with a sodium thiosulfate solution with a concentration of C1 until the blue color disappears as the end point, and the volume of the sodium thiosulfate solution consumed by the sample solution is V3.

[0034] Specifically, 50 mL of the sample solution was taken into a 250 mL conical flask, 6 mL of (1+1) hydrochloric acid and 0.5 g of ammonium persulfate were added, and the solution was heated and evaporated to 10 mL to oxidize all the iron ions in the sample solution to trivalent iron ions. After cooling, 2 g of potassium iodide was added, 50 mL of 70°C hot water was added, 1 mL of 1% starch indicator was added, and the solution was titrated with 0.1 mol / L sodium thiosulfate solution until the blue color disappeared as the end point. The volume of the sodium thiosulfate solution consumed by the sample solution was V3.

[0035] Step S140, obtain the volume of sodium thiosulfate solution consumed by pure water: absorb pure water with a volume of V2 into a conical flask, add hydrochloric acid and ammonium persulfate, heat and evaporate, add potassium iodide after cooling, add hot water, add starch indicator, and titrate with sodium thiosulfate solution with a concentration of C1 until the blue color disappears as the end point, and the volume of sodium thiosulfate solution consumed by pure water is V4.

[0036] Specifically, 50 mL of pure water was taken into a 250 mL conical flask, 6 mL of (1+1) hydrochloric acid and 0.5 g of ammonium persulfate were added, and the mixture was heated and evaporated to 10 mL. After cooling, 2 g of potassium iodide was added, 50 mL of 70°C hot water was added, 1 mL of 1% starch indicator was added, and the mixture was titrated with 0.1 mol / L sodium thiosulfate solution until the blue color disappeared, and the volume of the sodium thiosulfate solution consumed by the pure water was V3.

[0037] Step S150, determining the percentage content of iron oxide impurities in brown corundum: determining the percentage content W of iron oxide impurities in brown corundum according to M, V1, V2, V3, C1 and V4.

[0038] Reference Figure 3 , Figure 3 for Figure 1 FIG. 1 is a schematic diagram of an embodiment of a detailed process of step S150, wherein step S150 includes but is not limited to: Step S310, obtaining the percentage of trivalent iron ions in the sample solution: obtaining the percentage of trivalent iron ions C2 in the sample solution according to V2, V3, C1 and V4; Step S320, determining the percentage content of iron oxide impurities in brown corundum: determining the percentage content W of iron oxide impurities in brown corundum according to C2, M, and V1.

[0039] Specifically, in step S310, the following formula is used to calculate according to V2, V3, C1 and V4 to obtain the percentage content C2 of trivalent iron ions in the sample solution:

[0040] Where: C1 represents the concentration of sodium thiosulfate solution, in mol / L; V3 represents the volume of sodium thiosulfate solution consumed by the sample solution, in mL; V4 represents the volume of sodium thiosulfate solution consumed by pure water, in mL; 0.05585 represents the mass of Fe equivalent to 1.00 mL of sodium thiosulfate standard solution [C(Na2S2O3)=1.000 mol / L], where the unit of the mass of iron is g; V2 is the volume of the sample liquid absorbed in step S130, and the unit is L.

[0041] In step S320, the percentage content W of iron oxide impurities in brown corundum is calculated using the following formula according to C2, M, and V1:

[0042] Where: V1 represents the total volume of the sample solution, in L; 0.6995 represents the proportion of iron in the iron oxide molecule; M represents the mass of brown corundum used for digestion, in g.

[0043] The method for detecting the content of iron oxide impurities in brown corundum described in the embodiment of the present application can detect the content of ferric oxide impurities in brown corundum simply, quickly and at a very low cost without using expensive instruments and without complicated operating steps.

[0044] The following is a detailed description of the method for detecting the iron oxide impurity content in the brown corundum described in the examples of the present application with specific examples. It is worth noting that the following description is only an exemplary description and is not a specific limitation of the present application.

[0045] Embodiment 1 Sampling: According to GB / T 4676-2018 “General Abrasive Sampling Method”, the brown corundum batch to be tested is sampled and reduced until a 100g brown corundum sample is obtained.

[0046] Grinding: Put 100g of brown corundum sample into a grinder for grinding, and grind until the particle size of the brown corundum sample is less than 10μm; Drying: Put the ground 100g brown corundum sample into an oven for drying.

[0047] Prepare the sample solution: weigh 10g of brown corundum sample and put it into the reactor lining, add 20mL of deionized water into the reactor lining, and slowly add 50mL of concentrated hydrochloric acid along the edge of the reactor lining, cover the reactor lining, tighten the reactor, put it into the oven, and react at 170℃ for 5 hours. After the reaction is completed, filter the sample solution with fast filter paper, and fully wash the reactor lining, and finally fix the volume to 250mL volumetric flask. Obtain the volume of sodium thiosulfate solution consumed by the sample solution: Pipette 50 mL of the sample solution into a 250 mL conical flask, add 6 mL (1+1) hydrochloric acid and 0.5 g ammonium persulfate, heat and evaporate to 10 mL to oxidize all the iron ions in the sample solution to trivalent iron ions. After cooling, add 2 g potassium iodide, 50 mL 70°C hot water, 1 mL 1% starch indicator, and titrate with 0.1 mol / L sodium thiosulfate solution until the blue color disappears as the end point. The volume of sodium thiosulfate solution consumed by the sample solution is 0.65 mL.

[0048] Obtain the volume of sodium thiosulfate solution consumed by pure water: absorb 50 mL of pure water into a 250 mL conical flask, add 6 mL of (1+1) hydrochloric acid and 0.5 g of ammonium persulfate, heat and evaporate to 10 mL, add 2 g of potassium iodide after cooling, add 50 mL of 70°C hot water, add 1 mL of 1% starch indicator, and titrate with 0.1 mol / L sodium thiosulfate solution until the blue color disappears as the end point. The volume of sodium thiosulfate solution consumed by pure water is 0.02 mL.

[0049] Obtain the percentage of trivalent iron ions in the sample solution: According to V2, V3, C1 and V4, obtain the percentage of trivalent iron ions C2 in the sample solution:

[0050] Determine the percentage of iron oxide impurities in brown corundum: According to C2, M, V1, determine the percentage of iron oxide impurities in brown corundum W:

[0051] Embodiment 2 Example 2 uses the same brown corundum sample, and the only difference from Example 1 is that in this embodiment, the reaction temperature when preparing the sample solution is 190° C., and the volume of the sodium thiosulfate solution consumed to obtain the sample solution is 0.67 mL.

[0052] Therefore, the percentage of trivalent iron ions in the sample solution is C2:

[0053] The percentage of iron oxide impurities in brown corundum W:

[0054] Embodiment 3 Example 3 uses the same brown corundum sample, and the only difference from Example 1 is that in this embodiment, the reaction temperature when preparing the sample solution is 210° C., and the volume of the sodium thiosulfate solution consumed to obtain the sample solution is 0.69 mL.

[0055] Therefore, the percentage of trivalent iron ions in the sample solution is C2:

[0056] The percentage of iron oxide impurities in brown corundum W:

[0057] It can be seen from Examples 1 to 3 that the impurity content of iron oxide in brown corundum measured by the method for detecting the impurity content of iron oxide in brown corundum described in the examples of the present application is basically consistent with the inspection result of the XRF equipment, meeting the requirements for the detection of iron oxide in brown corundum.

[0058] The method for detecting the content of iron oxide impurities in brown corundum described in the embodiment of the present application can detect the content of ferric oxide impurities in brown corundum simply, quickly and at a very low cost without using expensive instruments and without complicated operating steps.

[0059] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0060] The embodiments of the present application are described in detail above in conjunction with the accompanying drawings, but the present application is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present application.

Claims

1. A method for detecting the content of iron oxide impurities in brown corundum, characterized in that: include: Sampling: Sampling and reducing the brown corundum batch to be tested to obtain brown corundum samples; Prepare the sample solution: weigh a brown corundum sample with a mass of M and put it into a reactor, add deionized water and concentrated hydrochloric acid, react to obtain a sample solution with a volume of V1; Obtain the volume of sodium thiosulfate solution consumed by the sample solution: draw a sample solution with a volume of V2 into a conical flask, add hydrochloric acid and ammonium persulfate, heat and evaporate, oxidize all the iron ions in the sample solution to trivalent iron ions, add potassium iodide after cooling, add hot water, add starch indicator, and titrate with a sodium thiosulfate solution with a concentration of C1 until the blue color disappears as the end point, and the volume of sodium thiosulfate solution consumed by the sample solution is V3; Obtain the volume of sodium thiosulfate solution consumed by pure water: draw pure water with a volume of V2 into a conical flask, add hydrochloric acid and ammonium persulfate, heat and evaporate, add potassium iodide after cooling, add hot water, add starch indicator, and titrate with sodium thiosulfate solution with a concentration of C1 until the blue color disappears as the end point, and the volume of sodium thiosulfate solution consumed by pure water is V4; Determine the percentage of iron oxide impurities in brown corundum: Determine the percentage W of iron oxide impurities in brown corundum based on M, V1, V2, V3, C1 and V4.

2. The method for detecting the iron oxide impurity content in brown corundum according to claim 1, characterized in that: During sampling, the brown corundum of the batch to be tested is sampled and divided until a 100g brown corundum sample is obtained.

3. The method for detecting the iron oxide impurity content in brown corundum according to claim 2, characterized in that: After sampling is completed and before preparing the sample solution, it also includes: Grinding: Grind 100g of brown corundum sample; Drying: Dry the brown corundum sample.

4. The method for detecting the iron oxide impurity content in brown corundum according to claim 3, characterized in that: During grinding, 100 g of the brown corundum sample is put into a grinder for grinding, and ground until the particle size of the brown corundum sample is less than 10 μm.

5. The method for detecting the iron oxide impurity content in brown corundum according to claim 4, characterized in that: In the preparation of the sample solution, weigh 10g of brown corundum sample and put it into the lining of the reactor, add 20mL of deionized water to the lining of the reactor, and slowly add 50mL of concentrated hydrochloric acid along the edge of the lining of the reactor, cover the lining of the reactor, tighten the reactor, put it in an oven for reaction, and obtain 250mL of sample solution.

6. The method for detecting the iron oxide impurity content in brown corundum according to claim 5, characterized in that: In preparing the sample solution, the reaction temperature is 170-210° C. and the reaction time is 5-8 hours.

7. The method for detecting the iron oxide impurity content in brown corundum according to claim 5, characterized in that: In preparing the sample solution, after the reaction is completed, the sample solution is filtered using a rapid filter paper, and the lining of the reactor is fully washed, and finally the volume is fixed to a 250 mL volumetric flask.

8. The method for detecting the iron oxide impurity content in brown corundum according to claim 5, characterized in that: In obtaining the volume of sodium thiosulfate solution consumed by the sample solution, aspirate 50 mL of the sample solution into a 250 mL conical flask, add 6 mL (1+1) hydrochloric acid and 0.5 g of ammonium persulfate, heat and evaporate to 10 mL to oxidize all the iron ions in the sample solution to trivalent iron ions. After cooling, add 2 g of potassium iodide, 50 mL of 70°C hot water, 1 mL of 1% starch indicator, and titrate with 0.1 mol / L sodium thiosulfate solution until the blue color disappears as the end point. The volume of sodium thiosulfate solution consumed by the sample solution is V3.

9. The method for detecting the iron oxide impurity content in brown corundum according to claim 8, characterized in that: To obtain the volume of sodium thiosulfate solution consumed by pure water, absorb 50 mL of pure water into a 250 mL conical flask, add 6 mL of (1+1) hydrochloric acid and 0.5 g of ammonium persulfate, heat and evaporate to 10 mL, add 2 g of potassium iodide after cooling, add 50 mL of 70°C hot water, add 1 mL of 1% starch indicator, and titrate with 0.1 mol / L sodium thiosulfate solution until the blue color disappears as the end point. The volume of sodium thiosulfate solution consumed by pure water is V4.

10. The method for detecting the iron oxide impurity content in brown corundum according to claim 1, characterized in that: In determining the percentage of iron oxide impurities in brown corundum, include: Obtaining the percentage of trivalent iron ions in the sample solution: according to V2, V3, C1 and V4, obtaining the percentage of trivalent iron ions C2 in the sample solution; Determine the percentage of iron oxide impurities in brown corundum: According to C2, M, and V1, determine the percentage W of iron oxide impurities in brown corundum.

Citation Information

Patent Citations

  • Determination method for metal iron and ferrous iron in direct reduction vanadium-titanium ore

    CN103323449A

  • Method for determination of content of ferric oxide

    CN107796804A